2007
DOI: 10.1002/dneu.20400
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal and environmental control of song control region growth and new neuron addition in adult male house finches, Carpodacus mexicanus

Abstract: In songbirds, testosterone (T) mediates seasonal changes in the sizes and neuroanatomical characteristics of brain regions that control singing (song control regions; SCRs). One model explaining the mechanisms of the growth of one SCR, the HVC, postulates that in the spring increasing photoperiod and circulating T concentrations enhance new neuron survival, thus increasing total neuron number. However, most research investigating the effects of T on new neuron survival has been done in autumn. The present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 42 publications
2
19
2
Order By: Relevance
“…Multiple studies later showed that treatment with exogenous T of photoregressed or gonadectomized subjects of both sexes largely mimics this effect therefore demonstrating the causal role of T in this aspect of neuroplasticity (Sartor et al, 2005; Smith et al, 1997; Strand and Deviche, 2007). However, no study has to our knowledge directly tested whether identical treatments with exogenous T have identical effects on the morphology of the song-control system in both male and female canaries.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies later showed that treatment with exogenous T of photoregressed or gonadectomized subjects of both sexes largely mimics this effect therefore demonstrating the causal role of T in this aspect of neuroplasticity (Sartor et al, 2005; Smith et al, 1997; Strand and Deviche, 2007). However, no study has to our knowledge directly tested whether identical treatments with exogenous T have identical effects on the morphology of the song-control system in both male and female canaries.…”
Section: Discussionmentioning
confidence: 99%
“…In castrated male starlings, American tree sparrows, and dark-eyed juncos and Gambel's whitecrowned sparrows, LD photoperiod is sufficient to promote at least partial growth of some song control system nuclei volumes (Bernard et al, 1997;Smith et al, 1997;Bentley et al, 1999;Dloniak and Deviche, 2001). In castrated male house finches, LD photoperiod is sufficient to induce growth of RA but not HVC (Strand and Deviche, 2007). More recent data testing this hypothesis comes from Gambel's white-crowned sparrows, where LD photoperiod accelerates the systemic T-induced increase in spontaneous firing rate and soma size in the nucleus RA (Meitzen et al, 2007a).…”
Section: Photoperiod May Modulate the Growth Of The Song Control Systemmentioning
confidence: 99%
“…In some species these brain regions are also responsive to changes in photoperiod absent from changes in T (Nottebohm, 2002;Strand & Deviche, 2007;Strand et al, 2009;Ball & Balthazart, 2010). Still, T directly affects these song control regions, independent from photoperiod, to modulate plasticity and induce singing behaviors (Dloniak & Deviche, 2001).…”
Section: Neuroplasticity and Androgensmentioning
confidence: 99%
“…This increase in neuron lifespan leads to larger numbers of neurons in the HVC where they can induce changes to behavior such as the seasonal increases in song. After the breeding season, T levels drop and apoptosis increases within the HVC which attenuates male songbird singing behavior (Rasika et al, 1994;Kirn et al, 1994;Nottebohm, 2002;Strand & Deviche, 2007). The neuroplasticity within the song control nuclei is therefore mediated by seasonal and hormonal changes, and these changes in the brain can lead to changes in behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation